The 4.2 ka event and its resulting cultural interruption in the Daihai Lake basin at the East Asian summer monsoon margin. (30th August 2019) - Xiao, Jule; Zhang, Shengrui; Fan, Jiawei; Wen, Ruilin; Xu, Qinghai; Inouchi, Yoshio; Nakamura, Toshio
Abstract: The 4.2 ka event has attracted worldwide interest since it was suggested to be a possible cause for the collapse of ancient civilizations. With the accumulation of proxy records, however, both the nature of the 4.2 ka event itself and the manner of societal responses to climate change have become controversial. Here we present a climatic record of Daihai Lake spanning 5–3 cal ka BP, together with a cultural series for the lake basin around 4 cal ka BP, to explore the regional nature of the 4.2 ka event and the relationship between climatic variation and cultural evolution. The climatic record reflects a dry event at the interval of 4060–3690 cal yr BP that could be a regional manifestation of the 4.2 ka event. The cultural series suggests an interruption between two different cultures during the period of 4300–4000 cal yr BP. Taking into consideration the dating errors and especially the uncertainties resulting from dating cultural layers of the archaeological sections, we suggest that the cultural interruption in the Daihai Lake basin might have been caused by a monsoon-related dry event. Humans primarily engaged in agriculture likely left the lake basin because the drainage basin became unsuitable for agrarian activities as the climate became too dry, thus leaving a cultural vacancy of several centuries in the lake basin. A significant decline in the intensity of the East Asian summer monsoon on centennial to multi-decadal timescales could be associated with dramatic cooling of surface waters of both the North Atlantic and western tropical Pacific.